Essentials of marketing research : - Malhotra, Naresh K. (Pearson, 2015)
This text provides a better teaching and learning experience–for you and your students. It will help you to: give students a framework for understanding, emphasize practical applications, foster interest through contemporary content, enable student success via learning aids.